Application of USB for Communication Verification Device in Theodolite. Issue 1 (January 2020) - Li, Xinghong; Zhang, Lingling; Lei, Yongfeng
Abstract: It is primary that difficult to verify the data for a long time in the data communication system of present theodolite. So take advantage of CY7C68013 to Designing the data communication verification device and composing the program for the test of the data communication verification. It is profitable to realize the data communication of theodolite and the realtime or later verificate data, and making the debugging more convenient. Meantime realize the high speed transmission.